Solvable model of the coherent synchrotron radiation effects in a four-bend chicane compressor - Fancong Zeng; Yi Jiao; Weihang Liu; Cheng-Ying Tsai (New Journal of Physics)
Electron beams with high peak currents are essential for x-ray free-electron lasers (FELs), and generally realized through multi-stage compression with four-bend symmetric C-shape chicanes. However, along with the beam compression, coherent synchrotron radiation (CSR) effects arise and may cause significant phase space distortion, which is considered as one of the greatest challenges to the beam and machine performance. It is highly desirable to suppress or even cancel the CSR effects in a chicane using the simplest possible methods. In this paper, for the first time we build an analytical framework for characterizing the CSR effects in a generic four-bend chicane, resulting in the proposal of a novel four-bend CSR-suppressed chicane. With this solvable model, the design and adjustment of such a CSR-suppressed chicane can be accomplished based on analytical formulas, as in a symmetric C-chicane. Numerical simulations demonstrate that compared to the C-chicane, a compressed beam with three times higher peak current and similar emittance growth can be achieved with the proposed chicane. We believe that this study provides a promising pathway for compressing electron bunch with minimal degradation of beam quality, benefiting future development of FELs and other types of accelerator-based facilities.